Petrochemistry and Tectonic Setting of the Phroa-Wiang Pa Pao Granitic Rocks, Chiang Mai, and Chiang Rai Provinces, Central Granitic Belt of Thailand - Jundee, Patcharin Kosuwan; Chaiwchan, Sunanthawat; Inthacharoensarn, Sumalee; Phajuy, Burapha; Nontarak, Pramote (Trends in Sciences, 2024)
The Phrao-Wiang Pha Phao granitic rocks are crop out along Highway Number 1150 (Phrao-Wiang Pa Pao) in Chiang Mai and Chiang Rai provinces. The geologic investigation as field observation, lithology, petrography, geochemistry, and tectonic interpretation applied for this study. The least-altered 19 rock samples were collected and performed in stained rock slabs for modal analysis and standard thin sections for petrographic analysis. Based on the Quartz-Alkali Feldspar-Plagioclase diagram for plutonic rocks, the rock samples in the Phrao area are granodiorite, and one is biotite-monzogranite, while most of the rock samples in the Wiang Pa Pao area are biotite-monzogranite. The petrographic investigation for rock samples indicated that granitic samples have medium to coarse-grained and show porphyritic texture. The orthoclase phenocrysts are sitting in the groundmass and are composed of quartz, plagioclase, and orthoclase feldspar, with a minor amount of biotite, muscovite, apatite, zircon, titanite, and opaque minerals. The granitic samples can be classified as granodiorite to monzogranite, which is high-K calc-alkalic affinity and peraluminous S-type based on geochemistry. Based on the normative mineralogy calculation, the rock samples were composed mainly of normative quartz, plagioclase, and orthoclase, with minor corundum, hypersthene, magnetite, ilmenite, apatite, zircon, and chromite. The S-type granitoid supported by normative corundum and Na2O/K2O ratios less than 0.49 at Na2O ranging from 1.53 - 2.35 wt %. Their tectonic setting of formation appears to be a post-orogenic environment (post-collisional granite) of the Sibumasu and the Indochina blocks. The Phrao Phrao-Wiang Pha Phao granitic rocks are a part of the Central Granitic Belt and are related to tin-tungsten deposits with rare earth elements. HIGHLIGHTS Tectonic setting of the Phroa-Wiang Pa Pao Granitic Rocks, Thailand. Petrography and modal analysis The geochemistry analysis by XRF and CIPW normative calculation. The Central Granitic Belt in Thailand. GRAPHICAL ABSTRACT